Towards a Healthy Architecture: A New Paradigm in the Design and Construction of Buildings. - Quesada-García, Santiago; Valero-Flores, Pablo; Lozano-Gómez, María (MDPI, 2023)
The recent COVID-19 pandemic has catalysed a new awareness of what living and working spaces should look like from a different perspective, and healthier cities and architecture have arisen because of inescapable public demand. Society has become clearly aware that there are still unhealthy concentrations within its environment. Spaces in cities are still being built that can favour the spread of diseases, in addition to using harmful construction materials. Living spaces must not only be sustainable, functional, and aesthetically beautiful but also comfortable, safe, and accessible, and, above all, they must be healthy. Healthy architecture has emerged as a new paradigm. This is the subject area of this work. This paper describes and develops the nature of this concept and proposes a novel definition of healthy architecture, aiming to compile state-of-the-art knowledge with a qualitative empirical and multi-method process, using case studies. This article provides a global perspective on new approaches and proposes a Decalogue with the basic principles that an environment or building must comply with in order to be healthy. The main contribution is to establish the basis for the creation of a new healthy architecture epistemology, focussing on cognitive, emotional, and physiological stimuli. This paper can help health professionals, designers, and architects, as well as companies and public administrations, to follow an innovative path in the planning of healthier cities and buildings.
Keywords: Construcción - Desarrollo; Salud pública; Vivienda y salud; Alzheimer, Enfermedad de - Aspectos ambientales; Healthy architecture; Wellbeing; Architecture and health; Healthy environments; Neuroarchitecture; Salutogenesis; Physiological architecture; Buildings for Alzheimer’s disease; Public health